Malaysia Run: The Development of a Mobile Game Application to Promote Malaysia Culture using Gamification Approach - Teoh, Suet Mun Sharon; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2022)
Malaysia is a beautiful country and contains interesting information that is worthy of being known by everyone. Many local movies produced to promote Malaysian local cultures to people all around the world. However, there is no game application focus on this purpose. Furthermore, due to the Coronavirus Disease 2019 (COVID-19) pandemic, the implementation of the travel restrictions had stopped everyone from travelling to other countries, even though in Malaysia. Children can only learn about these cultures on the book and website but not visiting each state. Therefore, Malaysia Run is designed based on the gamification approach and developed for the Android platform to allow children enjoys playing the game while absorbing new knowledge. This game consists of 6 levels which introduce six regions of Malaysia: Northern Region, Central Region, East Coast, Southern Region, Sabah, and Sarawak. Moreover, Game Development Live Cycle Model (GDLC) is chosen as the methodology, while Unity Game Engine and C# programming language are used to develop this application. Malaysia Run has conducted Alpha Testing, as well as Beta Testing by involving ten target users aged between 6 and 12 years old. The findings indicate the level of user acceptance is high by receiving satisfactory results with 92.6% positive feedback. The objectives of this project have been achieved, and its advantages and limitation are identified. Next, there are few improvements that could be made in future to enhance the game. Lastly, perhaps Malaysia Run can be continuously improved and really helps children to understand more about Malaysia.